Rapid Deterioration of Latent HBV Hepatitis during Cushing Disease and Posttraumatic Stress Disorder after Earthquake - Tashiro, Ryosuke; Ogawa, Yoshikazu; Tominaga, Teiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Reactivation of the hepatitis B virus (HBV) is a risk in the 350 million HBV carriers worldwide. HBV reactivation may cause hepatocellular carcinoma, cirrhosis, and fulminant hepatitis, and HBV reactivation accompanied with malignant tumor and/or chemotherapy is a critical problem for patients with chronic HBV infection. Multiple risk factors causing an immunosuppressive state can also induce HBV reactivation.We present a case of HBV reactivation during an immunosuppressive state caused by Cushing disease and physical and psychological stress after a disaster. A 47-year-old Japanese woman was an inactive HBV carrier until the Great East Japan Earthquake occurred and follow-up was discontinued. One year after the earthquake she had intractable hypertension, and her visual acuity gradually worsened. Head magnetic resonance imaging showed a sellar tumor compressing the optic chiasm, and hepatic dysfunction with HBV reactivation was identified. Endocrinologic examination established the diagnosis as Cushing disease. After normalization of hepatic dysfunction with antiviral therapy, transsphenoidal tumor removal was performed that resulted in subtotal removal except the right cavernous portion. Steroid hormone supplementation was discontinued after 3 days of administration, and gamma knife therapy was performed for the residual tumor. Eighteen months after the operation, adrenocorticotropic hormone and cortisol values returned to normal. The patient has been free from tumor regrowth and HBV reactivation throughout the postoperative course.Accomplishment of normalization with intrinsic steroid value with minimization of steroid supplementation should be established. Precise operative procedures and careful treatment planning are essential to avoid HBV reactivation in patients with this threatening condition.
Keywords: Cushing disease; immunosuppression; hepatitis B; spontaneous reactivation